Animal studies on male fertility enhancing properties of plants in Malaysia: a review of the past 16 years - Abdul Razak, Redzuan Nul Hakim; Md Isa, Muhammad Lokman; Mat Yusof, Afzan; Abdul Wahab, Azantee Yazmie; Muhammad, Hussin; Ramli, Roszaman (BIOSAD.org., 2017)
Infertility is an issue of global and national public health concern. It is a worrying scenario with increasing number of prevalence in infertility. The importance of drugs of plant origin in the quest of fertility enhancing agents for the male from natural products has long been recognized. The present review is an attempt to summarize the fertility enhancing plants with various approaches which are: part of plant have been used, type of extract for isolating the compounds, different isolated compounds (active principles) along with different animal model used. The literature covered is of 16 years from 2000 to 2016 for around 12 plants showing improving fertility activity in males. In conclusion, this review will help other researchers in focusing future herb based drug discovery in improving fertility problem among male across the globe.